(untitled) (Global Journal of Management and Business Research, 2023)
The study s objective is to investigate the impact of Social Media-Based Brand Community Participation on the brand s image Besides the study also focuses on uncovering the mediating role of brand association and brand awareness For achieving the above objectives relevant pieces of literature were extensively studied and seven hypotheses were developed For collecting relevant data for the research a structured questionnaire was developed and administered through using online social media The study used convenience sampling to collect data from 445 customers who have access to social media platforms and who have participated in several fashion brands fan pages The study discovered that Social Media-Based Brand Community Participation SMBBCP is positively related to brand association and brand awareness however it has an insignificant relationship with brand image Besides the brand association is positively associated with brand image whereas brand awareness has a positive impact on brand association Moreover the study confirms that brand association mediates the relationship between SMBBCP and brand image aside from negotiating the relationship between brand awareness and brand image Further brand awareness mediates the relationship between SMBBCP and brand association The far-reaching implications of the research have been discussed concerning the scope of further studies Finally the study examines its limitations in generalizing the results and concludes with a conclusion